Renewable Energy at Chilean Universities: Is it Possible? - Mac-Lean Bravo, Claudia Alejandra; Vargas, L.; Reyes, C. (My University, 2020)
The concept of sustainable universities has gained increasing relevance and momentum in the recent decades. This has led Higher Education Institutions to incorporate the conceptualisation of sustainability in their teaching, research, campus operations and outreach realms. In such a way, that innovative projects regarding sustainable initiatives and clean technologies have arisen in many universities worldwide. In operational terms at Chilean Higher Education Institutions, it is possible to find endeavours related to renewable energy, greenhouse gas emissions, water management, energy efficiency, recycling systems, among others. In the present work, the case study of on grid solar photovoltaic projects at the University of Magallanes in Patagonia, and at the Faculty of Physical and Mathematical Sciences of the University of Chile in Santiago are described, in their conception and operation stages respectively. Additionally, these developments are analysed in light of context-based variables, considering latitude, funding and business models, technologies, and the corresponding electric systems characteristics.
Keywords: Outreach; Relevance; Sustainable Energy